Cardiovascular pathology in the handicapped patient - Manzoli, Ugo; PennestrÃ¬, F.; Ferrazza, A. (Medicina e Morale, 2024)
As is well known, the clinical definition of a handicapped patient is remarkably complex and extensive, encompassing numerous well-defined aetiological forms but also a wide range of cases in which the handicap is related to non-specific or unknown hereditary factors or to socio-economic and hygienic environmental factors.